Prakiraan Kesuburan Perairan Bali Dari Citra Satelit [Forecast Fertility Bali Waters From Satellite Imagery] - Sony Angga Satrya, Abdul Manan (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract Aplication Ocean Remote Sensing technology to many use for field fisheries, once use this technology in forecast fertility water. The aim of this study was to determine the feasibility of Bali coastal area for cage of pearl oyster culture. The method used is a descriptive method of data collection. Satellite image processing activities Aqua/Terra Modis starting with the collection of satellite image data from the database NASA via OceanColor Web site, the selection of a clean image data, and than download of satellite images. The first stages of image data processing are used software ENVI 4.7, with procedures are coloring the image, limiting the minimum and maximum temperatures and sea surface chlorophyll-a, and classifiying of the image based on the value of sea surface temperature. Sea surface temperature parameter determine the location of the cage of pearl oysters (Pinctada maxima) culture. Suitability of the location of the cage of pearl oyster culture on Bali coastal area, at coordinates 8° 33' 00.97 " - 8° 42' 05.30" South Latitude and 115° 18' 03.40 " - 115° 39 ' 03.21" East Longitude. Based on geographical, that the location in the southeastern Bali coastal area and on the northern area of Nusa Pennida island.